Factors Affecting the Cost Savings Rate of University Procurement - Ning, Yi-Zi (Archives of Business Research, 2023)
The procurement function is an essential part of a university’s operations, as it provides the necessary goods and services for academic and administrative activities.This paper explores the impact of different demand channels on cost savings rate in university procurement. Through surveying and analyzing the demand channels used in university procurement, this study finds that the use of multiple demand channels can improve procurement efficiency and performance, and help reduce procurement costs. Moreover, the quality of communication and information sharing between universities and suppliers, as well as the level of competition among suppliers for procurement contracts, affect the cost savings rate. The findings of this study will also provide important implications for university procurement practices, by helping universities make more informed decisions regarding the selection of procurement demand channels. Ultimately, the goal is to improve the efficiency and effectiveness of university procurement practices, which can lead to cost savings, improved procurement outcomes, and increased value for money.